2011
DOI: 10.4103/0976-3147.80102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant extracts on Alzheimer’s disease: An insight into therapeutic avenues

Abstract: Alzheimer's disease (AD) is a devastative neurodegenerative disorder which needs adequate studies on effective treatment options. The extracts of plants and their effect on the amelioration of AD symptoms have been extensively studied. This paper summarizes the mechanisms like acetylcholinesterase (AChE) inhibition, modification of monoamines, antiamyloid aggregation effect, and antioxidant activity which are actively entailed in the process of amelioration of AD symptoms. These effects are induced by extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 74 publications
0
46
0
1
Order By: Relevance
“…This opens a substantial therapeutic strategy for the treatment of AD by inhibiting YAP/Bax pathway [123]. A few plant extracts, carotenoids, antioxidants and Chinese traditional medicines such as SuHeXiang Wan [124] have shown neuroprotective effects but they need potential further studies to validate the neuroprotective effects [125,126]. Recently, it has been shown that 2-cyclopropylimino-3-methyl-1,3-thiazoline hydrochloride (KHG26377) has a protective role against the beta-amyloid (Ab 25-35 )-induced primary cortical neuronal cell neurotoxicity [127].…”
Section: Resultsmentioning
confidence: 98%
“…This opens a substantial therapeutic strategy for the treatment of AD by inhibiting YAP/Bax pathway [123]. A few plant extracts, carotenoids, antioxidants and Chinese traditional medicines such as SuHeXiang Wan [124] have shown neuroprotective effects but they need potential further studies to validate the neuroprotective effects [125,126]. Recently, it has been shown that 2-cyclopropylimino-3-methyl-1,3-thiazoline hydrochloride (KHG26377) has a protective role against the beta-amyloid (Ab 25-35 )-induced primary cortical neuronal cell neurotoxicity [127].…”
Section: Resultsmentioning
confidence: 98%
“…The studies have shown that regular consumption of lemon balm infusions by people suffering from Alzheimer's disease positively influences their cognitive functions and relieves the symptoms of senile dementia. What is more, lemon balm may lower the level of cholesterol in blood and therefore prevent atherosclerosis [22,23].…”
Section: Lemon Balm (Melissa Officinalis)mentioning
confidence: 99%
“…Las hojas, cuyo consumo incluso en altas cantidades carecen de toxicidad, se han encontrado que poseen antioxidantes como las vitamina C y E, mejoran la memoria por medios nootropicos; se sospecha que podría ser utilizado para el tratamiento del Alzheimer según la investigación realizada por Obelesu M y col (6).…”
Section: Introduccionunclassified